2016
DOI: 10.1007/s11060-016-2265-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience of the concurrent use of radiosurgery and T-DM1 for brain metastases in HER2-positive metastatic breast cancer

Abstract: This is preliminary study assessing the efficacy and safety of concurrent use of radiation therapy (RT) and T-DM1 for the treatment of brain metastases (BM) in patients with HER2-positive metastatic breast cancer (BC). We retrospectively studied 12 patients treated for BM at the Institut Curie in 2014-2015 with T-DM1 and concurrent (4) or sequential (8) radiosurgery with or without whole brain irradiation. The following variables were studied: local control, clinical and radiological response as well as early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…The most commonly reported AEs in both groups was radiation necrosis (RN) with an incidence of 50% and 28.6%, for both T-DM1 during treatment and T-DM1 discontinued before SRS, respectively. Therefore, the combination of T-DM1 with SRS induced a clinically relevant increase in the risk of RN, when compared to previously published data [38][39][40]. Moreover, Carlson et al [40] found an association with cerebral swelling in patients on T-DM1 who underwent SRS.…”
Section: T-dm1 and Stereotactic Radiosurgerymentioning
confidence: 74%
See 1 more Smart Citation
“…The most commonly reported AEs in both groups was radiation necrosis (RN) with an incidence of 50% and 28.6%, for both T-DM1 during treatment and T-DM1 discontinued before SRS, respectively. Therefore, the combination of T-DM1 with SRS induced a clinically relevant increase in the risk of RN, when compared to previously published data [38][39][40]. Moreover, Carlson et al [40] found an association with cerebral swelling in patients on T-DM1 who underwent SRS.…”
Section: T-dm1 and Stereotactic Radiosurgerymentioning
confidence: 74%
“…Preliminary experience of the concurrent use of SRS and T-DM1 has recently been published [38]. Authors compared patients from 2 groups, patients who received T-DM1 during SRS and those with sequential treatment, where T-DM1 treatment was interrupted prior to SRS.…”
Section: T-dm1 and Stereotactic Radiosurgerymentioning
confidence: 99%
“…Most patients underwent T-DM1 concurrent with any SRS treatment, though this was not always concurrent with the course of SRS, which later resulted in CSRN. A recent publication by Geraud and colleagues retrospectively reviewed 12 patients treated for brain metastases with T-DM1, four of whom received this concurrently with SRS and eight sequentially (10). In the concurrent group 50% of patients (2 patients) had radionecrosis as compared with only 28.6% in the sequential group.…”
Section: Discussionmentioning
confidence: 99%
“…Although both SRS and T-DM1 are important therapies for HER2 þ populations with brain metastases, a number of series, including a previous report from our institution, have suggested increased rates of clinically significant radionecrosis (CSRN) with their combination (9,10). Given clinical findings consistent primarily with edema, and the known role of Aquaporin-4 (Aqp4) in neuroinflammation, we further focused on Aqp4 changes after therapy.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, I want to congratulate Geraud et al [1] for their study. They evaluated the efficacy and safety of concurrent use of radiation therapy (RT) and T-DM1 for the treatment of brain metastases (BM) in patients with HER2-positive metastatic breast cancer (BC).…”
mentioning
confidence: 99%